Board Diversity and Government Link Company Performance: the Case of Emerning Country - Putri Alberty; Zaitul Zaitul; Daniati Puttri; Desi Ilona (Journal Markcount Finance, 2023)
The importance of board diversity to improve company performance has been documented by previous researhers. However, prior research failed to emphasise government link company. Therefore, this paper investigates the effect board diversity on performance of government link company in Indonesia. We use the supervisory board diversity since we have two tier Board in Indonesia corporate governance system. In addition, Board Diversity composed of four: tenure, age educational and gender diversity. The data is collected from the annual report and financial statement of the company. This kind of data was taken from Indonesia’s stock exchange website, company sites and other electronic sources. Board diversity is measured by Blau Index and firm performance is measured by four proxies: accounting performance (ROA and ROE), and market performance (Stock return and Tobin’s Q). The multiple regression analysis is applied to analyze the data.  this study reveals that there is no effect of the board diversity on performance of government link company except board gender diversity for Tobin’s Q model. In addition, one control variable (company leverage) consistently for all models has a significant effect on company performance. This study has practical and theoretical implications, and it has been discussed in the paper. We suggest to the future investigator to add the research samples and consider other board diversity as factors affecting performance.